When "expatriation" is a matter of family. Opportunities, barriers and intimacies in international mobility - Cangià, Flavia; Zittoun, Tania (Migration Letters, 2018)
This special issue aims at understanding “expatriate” mobility with a special focus on the role of family and intimacy, and brings together different case-studies, built through different theoretical perspectives. These allow approaching “expatriate” mobile families along two main lines: as part of the making of life trajectories, and as these are shaped by, and are shaping, professional trajectories. This editorial highlights the contributions of the various articles, before addressing a series of emerging issues. Among these, it questions the very notion of “expatriate” in the light of family life, shows the evolution of families in repeated mobility, and brings to the fore the importance of temporality and timing in these family lives, as well as that of reflexivity in mobility. As a whole, the various contributions of this special issue complement each other in illustrating the complexities of expatriates’ migration and family life in times of increasing global mobility, but also, they raise theoretical discussions, point to possible empirical implications, and suggest avenues for further investigations.